A luminescent material and its preparation method and application
The luminescent materials containing zero-dimensional CsCu2I3 particles were prepared through Tongxuan electrospinning technology, which solved the problems of harsh preparation conditions and unstable performance in the prior art, and achieved efficient and stable luminescent performance and environmental stability.
Patent Information
- Application Number
- CN202411677116.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In the prior art, the preparation conditions of the copper-based perovskite iodide CsCu2I3 material are harsh, and the prepared materials have problems such as large size, poor environmental stability, and unstable photoluminescent performance.
A luminescent material containing zero-dimensional CsCu2I3 particles was prepared by coaxial electrospinning method. By dispersing the copper-based perovskite precursor in the presence of hypophosphoric acid, and mixing it with polymers to form an internal and external bilayer structure of light emitting fibers.
It has achieved the preparation of luminescent materials with excellent and stable luminescent properties and environmental stability. The fluorescence intensity remains unchanged in water, the photoluminescent quantum yield is high (can reach 25.6%), and is suitable for optical pump yellow light LED devices and flexible X-ray imaging.
Smart Images

Figure CN119177503B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a luminescent material and a preparation method and application thereof. Background Art
[0002] Halide perovskites are considered one of the most attractive research hotspots in the field of perovskite optoelectronic applications due to their high photoluminescence quantum yield (PLQY), tunable emission wavelength and good carrier mobility. Among them, the most studied halide perovskites are copper-based iodide perovskite materials: CsCu2I3, which can be used to prepare photodiode-type X-ray detectors, LED light emitters, fluorescent solar lasers, etc. For example, patent CN115188898A discloses a photodiode-type X-ray detector based on CsCu2I3 wafers, which mentions the use of hot pressing to prepare CsCu2I3 wafer materials, but the hot pressing pressure reaches 5-40 MPa, the temperature is 80-120 °C, and the holding time is as long as 2-10 h. The preparation conditions are harsh, and in the preparation process, additional additives (such as C60, graphite and black phosphorus) need to be introduced to modify the defects of the CsCu2I3 wafer and enhance the stability of the CsCu2I3 wafer. For example, patent CN113479927B discloses a method for synthesizing yellow light-emitting halogen perovskite CsCu2I3 powder in water. The CsCu2I3 powder prepared by this method, first, can only prepare micron-sized perovskite particles. Second, although CsCu2I3 has good thermal stability, it is still easy to decompose into CsI and CuI in a humid environment, which affects the luminescence properties. Perovskite particles with larger particle sizes are more difficult to be evenly dispersed in other substances such as polymers. Third, the optical property measurement results of the CsCu2I3 powder prepared by this method show that its luminescence performance is unstable, and there is a situation where the photoluminescence spectrum cannot be detected. Summary of the invention
[0003] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide a new method for preparing a luminescent material comprising zero-dimensional CsCu2I3 particles. The method is simple and easy to implement, and the luminescent material prepared can have both excellent and stable luminescent properties and environmental stability.
[0004] The present invention also provides a luminescent material prepared by the above preparation method and its application in the fields of flexible lighting, X-ray imaging, etc.
[0005] In order to achieve the above object, a technical solution adopted by the present invention is: a method for preparing a luminescent material, the preparation method comprising:
[0006] In the presence of hypophosphorous acid, a copper-based iodide perovskite precursor is dispersed in a first organic solvent to prepare a first mixed solution;
[0007] Mixing the high molecular polymer with a second organic solvent under heating conditions to prepare a second mixed solution;
[0008] Mixing part of the second mixed solution with the first mixed solution as an inner layer spinning solution, and using the remaining second mixed solution as an outer layer spinning solution, and spinning by a coaxial electrospinning method to obtain the luminescent material;
[0009] Wherein, the mass concentration of the copper-based iodide perovskite precursor in the inner layer spinning solution is controlled to be 0.07-0.28 g / mL;
[0010] The luminescent material is a luminescent fiber or a luminescent aggregate composed of a plurality of the luminescent fibers. The luminescent fiber includes an inner layer and an outer layer coated on the inner layer. The inner layer includes a polymer matrix and CsCu2I3 particles dispersed in the polymer matrix and present in nanometer size. The polymer matrix and the outer layer are each independently formed by a portion of the polymer. The CsCu2I3 particles are formed by converting the copper-based iodide perovskite precursor.
[0011] Furthermore, the mass concentration of the copper-based iodide perovskite precursor in the inner layer spinning solution is controlled to be 0.15-0.25 g / mL. Still further, the mass concentration of the copper-based iodide perovskite precursor in the inner layer spinning solution is controlled to be 0.17-0.23 g / mL.
[0012] In some preferred embodiments of the present invention, the mass concentration of the copper-based iodide perovskite precursor in the inner layer spinning solution is controlled to be 0.20-0.22 g / mL.
[0013] According to some preferred aspects of the present invention, the feed mass ratio of the copper-based iodide perovskite precursor to a portion of the high molecular polymer in the second mixed solution in the inner layer spinning solution is controlled to be 1.1-1.4:1.
[0014] According to some preferred aspects of the present invention, the mass ratio of the high molecular weight polymer in the inner layer spinning solution to the high molecular weight polymer in the outer layer spinning solution is 1:0.9-1.1, further 1:0.95-1.05. According to a specific aspect of the present invention, the mass ratio of the high molecular weight polymer in the inner layer spinning solution to the high molecular weight polymer in the outer layer spinning solution is 1:1.
[0015] In some embodiments of the present invention, the copper-based iodide perovskite precursor is composed of CsI and CuI, and the molar ratio of CsI to CuI is 1:2.0-2.05.
[0016] According to some preferred aspects of the present invention, based on 1 mmol of the CsI, the added amount of the hypophosphorous acid is 0.05-0.15 mL, and the hypophosphorous acid is added in the form of a hypophosphorous acid aqueous solution, and the mass fraction of the hypophosphorous acid aqueous solution is 40%-60%.
[0017] According to some preferred aspects of the present invention, the mass concentration of the high molecular weight polymer in the second mixed solution is controlled to be 0.1-0.6 g / mL, and further 0.1-0.5 g / mL.
[0018] According to some preferred aspects of the present invention, the first mixed solution and the inner layer spinning solution are respectively mixed at 20-30°C.
[0019] According to some preferred aspects of the present invention, the heating condition is controlled at a temperature of 50-80°C.
[0020] According to the present invention, the electrostatically spun luminescent fibers are in a fiber shape, and their diameter is nanometer-sized, and they can also be called luminescent nanofibers. When the spun luminescent fibers are collected in a certain area, a luminescent film can be obtained.
[0021] In the present invention, CsCu2I3 is an ionic crystal, and therefore exists in the form of precursor ions in the solution phase, and finally the solvent evaporates during the electrospinning process to form CsCu2I3 particles.
[0022] According to the present invention, a bonding layer is formed between the inner layer and the outer layer, and the bonding layer is formed by the mutual penetration of the high molecular polymers contained in the inner layer and the outer layer. Further, since the high molecular polymers used in the inner layer and the outer layer of the present invention are the same, it is more conducive to stable bonding between them.
[0023] According to the present invention, the photoluminescence quantum yield of the luminescent material is adjusted by the content of the CsCu2I3 particles, and the photoluminescence quantum yield shows a trend of first increasing and then decreasing as the content of the CsCu2I3 particles increases.
[0024] In some embodiments of the present invention, the process parameters of the coaxial electrospinning method include: a spinning voltage of 15-25 kV, a propulsion speed of 0.1-0.5 mL / h, and a receiving distance of 20-25 cm.
[0025] In the present invention, the operation process of the coaxial electrospinning method can be carried out with reference to the prior art. The principle is based on the electrospinning technology, which utilizes the coaxial structure of the inner and outer electrodes and the nozzle to stretch the polymer of the spinning solution into fibers with nanometer diameter under a voltage electric field. The specific process will not be described in detail here.
[0026] In some embodiments of the present invention, the high molecular polymer is a combination of one or more selected from polyvinylidene fluoride, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol.
[0027] In some embodiments of the present invention, the average weight-average relative molecular mass of the high molecular weight polymer is 100,000-2,000,000.
[0028] In some embodiments of the present invention, the first organic solvent and the second organic solvent include N,N-dimethylacetamide and / or N,N-dimethylformamide, respectively.
[0029] Another technical solution provided by the present invention is: a luminescent material prepared by the above-mentioned method for preparing the luminescent material.
[0030] Another technical solution provided by the present invention is a luminescent film, the preparation method of which comprises:
[0031] In the presence of hypophosphorous acid, a copper-based iodide perovskite precursor is dispersed in a first organic solvent to prepare a first mixed solution;
[0032] Mixing the high molecular polymer with a second organic solvent to prepare a second mixed solution;
[0033] Part of the second mixed solution is mixed with the first mixed solution as the inner layer spinning solution, and the remaining second mixed solution is used as the outer layer spinning solution. The solution is spun out by coaxial electrospinning and collected in a preset area to obtain a film-like luminescent film.
[0034] Another technical solution provided by the present invention is: a luminescent fiber, comprising an inner layer and an outer layer coated on the inner layer, the inner layer comprising a polymer matrix, CsCu2I3 particles dispersed in the polymer matrix and existing in nanometer size, the polymer matrix and the outer layer are each independently formed of a polymer, and the CsCu2I3 particles are formed by converting a copper-based iodide perovskite precursor.
[0035] Another technical solution provided by the present invention is: a luminescent fiber, the luminescent fiber comprising an inner layer and an outer layer coated on the inner layer, the inner layer comprising a polymer matrix, CsCu2I3 particles dispersed in the polymer matrix and existing in the form of nanometer size, the polymer matrix and the outer layer are independently formed of a polymer, and the CsCu2I3 particles are formed by converting a copper-based iodide perovskite precursor;
[0036] The photoluminescence quantum yield of the luminescent fiber is adjusted by the content of the CsCu2I3 particles in the luminescent fiber, and the photoluminescence quantum yield shows a trend of first increasing and then decreasing as the content of the CsCu2I3 particles increases.
[0037] Furthermore, in the inner layer, the mass ratio of the CsCu2I3 particles to the polymer matrix is 1.1-1.4:1.
[0038] Furthermore, in the luminescent fiber, the mass ratio of the CsCu2I3 particles to the high molecular polymer is 0.55-0.75:1.
[0039] Another technical solution provided by the present invention is: an application of the above-mentioned luminescent material, luminescent fiber or luminescent film in the preparation of a light-pumped yellow LED device.
[0040] Another technical solution provided by the present invention is: an application of the above-mentioned luminescent material, luminescent fiber or luminescent film in flexible X-ray imaging.
[0041] Furthermore, within the range of X-ray doses of 1.48 mGy / s to 11.84 mGy / s, further within the range of 1.48 mGy / s to 8 mGy / s, and further within the range of 1.48 mGy / s to 3 mGy / s, the luminescent material, luminescent fiber or luminescent film described above is used in flexible X-ray imaging.
[0042] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0043] Based on the harsh preparation conditions of the existing copper-based iodide perovskite materials, the prepared copper-based iodide perovskite CsCu2I3 materials have defects such as large size, poor environmental stability, unstable photoluminescence performance, etc., the present invention innovatively provides a luminescent material with a new structure and a preparation method thereof. The luminescent material with the new structure has an inner and outer double-layer structure, the inner layer structure is coated by the outer layer structure, the inner layer is mainly a polymer matrix and zero-dimensional CsCu2I3 particles uniformly dispersed in the polymer matrix and in nanometer size, and the outer layer is a flexible protective layer formed by a polymer. During the preparation, a first mixed solution containing a copper-based iodide perovskite precursor and hypophosphorous acid and a second mixed solution containing a polymer are prepared in steps, and then a part of the second mixed solution is mixed with the first mixed solution to form a protective film. The inner spinning solution is used, and the remaining second mixed solution is used as the outer spinning solution. The luminescent material of the novel structure is spun out in one step by a coaxial electrospinning method. The method is simple and can avoid the conversion of monovalent copper with fluorescent characteristics into divalent copper. In particular, the prepared luminescent material can have excellent environmental stability such as water / oxygen stability. Even if it is placed in water for a long time, the decrease in fluorescence intensity is very small. At the same time, the fluorescence quantum yield PLQY is high (can reach 25.6%), achieving high-efficiency luminescence efficiency in the yellow light band of the lead-free system, and the luminescent material of the novel structure has fewer defects and stable luminescence performance. In addition, the luminescent material of the present invention or its film-forming can be used directly, for example, it can be directly integrated with an ultraviolet light LED to form a light-pumped yellow light emitting device, and can also be used for ultra-low dose, flexible X-ray imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The bright field macroscopic photograph of the luminescent material prepared in Example 1 and the dark field fluorescence photograph (scale is 2 cm) under ultraviolet light (wavelength 320 nm);
[0045] Figure 2 The fluorescence spectrum and excitation spectrum of the luminescent material prepared in Example 1;
[0046] Figure 3 The SEM image and the corresponding EDS image of the luminescent fiber spun in Example 1 (the scale is 500 nm);
[0047] Figure 4 The X-ray diffraction pattern of the powder of the luminescent material prepared in Example 1 after being crushed;
[0048] Figure 5 This is a comparison chart of the fluorescence intensity of the luminescent material prepared in Example 1 and the commercial LYSO:Ce scintillator;
[0049] Figure 6 This is an image of the luminescent material prepared in Example 1 on a tiny circuit board circuit under low-dose (6 mGy / s) X-rays;
[0050] Figure 7 This is a diagram showing the lotus leaf effect of the luminescent material prepared in Example 1;
[0051] Figure 8 The SEM images of luminescent materials prepared using polyvinylidene fluoride with different molecular weights (scale bar is 10 μm);
[0052] Fig. 9 Bright field and dark field fluorescence microscope photos of the luminescent material prepared using polyvinyl pyrrolidone as a high molecular polymer (scale bar is 100μm);
[0053] Fig.10 Bright field and dark field fluorescence microscope photos of the luminescent material prepared using polyvinyl alcohol as a high molecular polymer (scale bar is 100μm);
[0054] Fig.11 Bright field and dark field fluorescence microscope photos of the luminescent material prepared using polyacrylonitrile as a high molecular polymer (scale bar is 100μm);
[0055] Fig.12 The fluorescence quantum yield distribution diagram of the luminescent material obtained by using different mass concentrations of the inner layer spinning solution;
[0056] Fig.13 The fluorescence photos and fluorescence spectrum change diagram of the luminescent material obtained by using polyvinylidene fluoride as a high molecular polymer placed in water for different days;
[0057] Fig.14 This is a working photo of a light-pumped yellow light emitting device constructed by directly using the luminescent material prepared in Example 1 and an ultraviolet LED;
[0058] Fig.15 This is a comparison chart of the fluorescence quantum yields of the luminescent materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0059] FIG16 is a stability test diagram of the luminescent material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0060] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0061] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art. In the following, the molecular weight of each polymer is the average weight average relative molecular mass.
[0062] Embodiment 1:
[0063] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0064] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0065] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.36 g / mL);
[0066] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0067] Embodiment 2:
[0068] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0069] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0070] S2, 1.0 g of 470,000 molecular weight polyvinylidene fluoride was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.36 g / mL);
[0071] S3. Mixed solution A and half of solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of the mixed solution B was 1.28:1), and the remaining half of solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0072] Embodiment 3:
[0073] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0074] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0075] S2, 1.0 g of 1 million molecular weight polyvinylidene fluoride was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.36 g / mL);
[0076] S3. Mixed solution A and half of solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of the mixed solution B was 1.28:1), and the remaining half of solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0077] Embodiment 4:
[0078] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0079] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.1 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in this solution, the total mass concentration of cesium iodide and cuprous iodide is 0.53 g / mL);
[0080] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 2.4 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.42 g / mL);
[0081] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.27 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0082] Embodiment 5:
[0083] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0084] S1. Ultrasonicate 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%) and 1.9 mL N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (the total mass concentration of cesium iodide and cuprous iodide in this solution is 0.32 g / mL);
[0085] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 4 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.25 g / mL);
[0086] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.16 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0087] Embodiment 6:
[0088] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0089] S1. Ultrasonicate 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%) and 2.8 mL N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (the total mass concentration of cesium iodide and cuprous iodide in this solution is 0.22 g / mL);
[0090] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 5.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.17 g / mL);
[0091] S3. Mixed solution A and half of solution B were stirred and mixed at room temperature to form an inner spinning solution (the total mass concentration of cesium iodide and cuprous iodide in the spinning solution was 0.11 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of the mixed solution B was 1.28:1). The remaining half of the mixed solution B was used as an outer spinning solution. The luminescent material was prepared by coaxial electrospinning. The luminescent fibers could be collected into a luminescent film. The spinning parameters were set as follows: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0092] Embodiment 7:
[0093] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0094] S1. Ultrasonicate 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%) and 4.5 mL N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (the total mass concentration of cesium iodide and cuprous iodide in this solution is 0.14 g / mL);
[0095] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 9.0 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.11 g / mL);
[0096] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.07 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0097] Embodiment 8:
[0098] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0099] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0100] S2, 1.0 g of 700,000 molecular weight polyvinyl pyrrolidone was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinyl pyrrolidone olefin was 0.36 g / mL);
[0101] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0102] Embodiment 9:
[0103] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0104] S1. Ultrasonicate 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0105] S2, 1.0 g of 700,000 molecular weight polyvinyl alcohol was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinyl alcohol was 0.36 g / mL);
[0106] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0107] Embodiment 10:
[0108] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0109] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide, 0.1 mL of hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL of N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (in which the total mass concentration of cesium iodide and cuprous iodide is 0.4 g / mL);
[0110] S2, 1.0 g of 220,000 molecular weight polyacrylonitrile was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyacrylonitrile was 0.36 g / mL);
[0111] S3. Mixed solution A and half of solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of the mixed solution B was 1.28:1), and the remaining half of the mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0112] Comparative Example 1:
[0113] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0114] S1. 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%), 0.5 g 600,000 molecular weight polyvinylidene fluoride and 2.9 mL N,N-dimethylacetamide were ultrasonically treated for 5 minutes, heated at 60 degrees Celsius and stirred evenly and used as the inner layer spinning solution; 0.5 g 600,000 molecular weight polyvinylidene fluoride was mixed with 1.4 mL N,N-dimethylacetamide, heated at 60 degrees Celsius and stirred evenly and used as the outer layer spinning solution.
[0115] S2. The luminescent material was prepared by coaxial electrospinning. The luminescent fibers could be collected into luminescent films. The spinning parameters were set as follows: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0116] Comparative Example 2:
[0117] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, and the specific steps are as follows:
[0118] S1. Ultrasonicate 0.26 g of cesium iodide, 0.38 g of cuprous iodide and 1.6 mL of N,N-dimethylacetamide for 5 minutes and mix them evenly to obtain a clear mixed solution A (the total mass concentration of cesium iodide and cuprous iodide in the solution is 0.40 g / mL);
[0119] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.36 g / mL);
[0120] S3. Mixed solution A and half of mixed solution B were stirred and mixed evenly at room temperature as the inner spinning solution (in the spinning solution, the total mass concentration of cesium iodide and cuprous iodide was 0.21 g / mL, and the total mass of cesium iodide and cuprous iodide to the mass ratio of polyvinylidene fluoride in half of mixed solution B was 1.28:1), and the remaining half of mixed solution B was used as the outer spinning solution. The luminescent material was prepared by coaxial electrospinning, and the luminescent fibers could be collected into a luminescent film. The spinning parameters were set as: voltage of 20 kV, receiving distance of 25 cm, and spinning speed of 0.25 mL / h.
[0121] Comparative Example 3:
[0122] This example provides a method for preparing a luminescent material and the luminescent material prepared therefrom, which is basically the same as that in Example 1, except that: in S3, the mixed solution A is directly mixed with the mixed solution B and then non-coaxial conventional electrospinning is performed.
[0123] The specific steps are as follows:
[0124] S1. Ultrasonicate 0.26 g cesium iodide, 0.38 g cuprous iodide, 0.1 mL hypophosphorous acid aqueous solution (mass fraction 50%) and 1.5 mL N,N-dimethylacetamide for 5 minutes, and mix them evenly to obtain a clear mixed solution A (the total mass concentration of cesium iodide and cuprous iodide in this solution is 0.4 g / mL);
[0125] S2, 1.0 g of 600,000 molecular weight polyvinylidene fluoride was mixed with 2.8 mL of N,N-dimethylacetamide, and heated and stirred at 60 degrees Celsius to obtain a clear mixed solution B (in which the mass concentration of polyvinylidene fluoride was 0.36 g / mL);
[0126] S3. Mixed solution A and mixed solution B are stirred and mixed evenly at room temperature as spinning solution for electrospinning. The spinning parameters are set as follows: voltage of 20 kV, receiving distance of 25 cm, spinning speed of 0.25 mL / h, and the luminescent fibers can be collected into luminescent films.
[0127] Performance Test:
[0128] The characteristics of the luminescent material disclosed in the present invention are that the CsCu2I3 nanoparticles are synthesized by configuring the solution in steps and then using the coaxial electrospinning technology and in-situ combined with the polymer matrix, and the zero-dimensional structure of the CsCu2I3 nanoparticles is uniformly embedded in the polymer matrix to form composite nanofibers, and a layer of polymer coating is also formed. Practice shows that this structure significantly improves the chemical stability and flexibility of the copper-based iodide perovskite material, especially the CsCu2I3 nanoparticles obtained in this way have fewer defects and stable and excellent luminescent performance. In addition, the luminescent material of the present invention is convenient for practical application, and a light-pumped yellow light emitting device can be directly constructed, and when used as an X-ray imaging film, the flexibility can achieve high resolution of X-ray imaging at ultra-low irradiation doses.
[0129] Figure 1 This is a macroscopic photograph of the luminescent material prepared in Example 1 ( Figure 1 The left side of the figure a) and the dark field fluorescence photograph under ultraviolet light (wavelength 320 nm) ( Figure 1 As shown in the right figure (b), the luminescent material in film form can be directly prepared by electrospinning, and a large-sized composite fiber membrane with a length and width of about 11 cm can be obtained. At the same time, it exhibits uniform and bright yellow light emission under ultraviolet light (wavelength 320 nm).
[0130] Figure 2 The fluorescence spectrum and excitation spectrum of the luminescent material prepared in Example 1. The fluorescence peak of the luminescent material is about 554 nm, the half-peak width is about 165 nm, and the optimal excitation wavelength is about 333 nm. As can be seen from the figure, the luminescent material of the present invention has a large Stokes shift and wide-spectrum emission, which effectively avoids the existence of the self-absorption problem (usually, excitons in perovskites are easily dissociated, and a small Stokes shift will lead to severe self-absorption), which is conducive to presenting excellent luminescence performance and is conducive to the construction of LED devices.
[0131] Figure 3 The SEM image of the luminescent fiber spun in Example 1 (specifically Figure 3 Figure a) and the corresponding EDS diagram (i.e., energy spectrum diagram, Figure 3 Figures b, c and d in the figure). The diameter of the luminescent fiber is about 460 nm, and the Cu, I and Cs elements are evenly distributed in the luminescent fiber with uniform size, indicating that the CsCu2I3 nanoparticles are evenly distributed in the fiber prepared by the electrospinning method. There are no obvious CsCu2I3 nanoparticles exposed on the fiber surface, indicating that the present invention has obtained an effective coating layer, which is beneficial to the protection of the CsCu2I3 nanoparticles.
[0132] Figure 4 This is the powder X-ray diffraction pattern of the crushed luminescent material prepared in Example 1. By comparing the standard PDF card of CsCu2I3, it is proved that the electrospinning method successfully realizes the synthesis of CsCu2I3 nanoparticles and the in-situ combination of CsCu2I3 nanoparticles and polymer matrix, and successfully prepares ultra-small CsCu2I3 nanoparticles.
[0133] Figure 5 The comparison of the radiation fluorescence intensity of the luminescent material prepared in Example 1 and the commercial LYSO:Ce scintillator (although the commercial material has good effect, it is expensive and uses more rare earth elements, etc.) shows that the radiation fluorescence intensity of the luminescent material of the present invention is close to that of the commercial scintillator. In the range of X-ray doses of 1.48 mGy / s to 11.84 mGy / s, the radiation fluorescence intensity of the luminescent material shows an increasing trend and exhibits good linearity, especially at low doses, the two are very close, indicating that the luminescent material of the present invention is particularly suitable for use at low doses.
[0134] Figure 6 From the imaging of the tiny circuit board circuit using the luminescent material prepared in Example 1 under low-dose (6 mGy / s) X-rays, it can be seen that the internal circuit is clearly visible; in fact, for smaller products, if their structure can be clearly seen under low doses, the effect of the luminescent material is better.
[0135] Figure 7 This is a diagram showing the lotus leaf effect of the luminescent material prepared in Example 1. It can be seen from the diagram that it has excellent hydrophobic properties.
[0136] Figure 8 The SEM images of luminescent materials prepared using polyvinylidene fluoride with different molecular weights are shown in FIG. Figure 8 The left side of the figure a is a luminescent material prepared using polyvinylidene fluoride with a molecular weight of 470,000 (Example 2). The diameter of the prepared fiber is about 380 nm. Figure 8 Figure b on the right side of the middle is a luminescent material prepared using polyvinylidene fluoride with a molecular weight of 1 million (Example 3). The diameter of the prepared fiber is about 850 nm, indicating that increasing the molecular weight will increase the diameter of the fiber.
[0137] Figure 9-11 Bright field (Figure a on the left) and dark field fluorescence microscope photographs (Figure b on the right) of luminescent materials prepared using polyvinyl pyrrolidone (Example 8), polyvinyl alcohol (Example 9) and polyacrylonitrile (Example 10) as polymers, respectively. Under ultraviolet light, the fibers exhibit uniform yellow light emission, indicating that this method has good universality for different polymers.
[0138] Fig.12 This is a distribution diagram of the fluorescence quantum yield of the luminescent material obtained using different mass concentrations of inner layer spinning solution (corresponding to Example 1, Example 4, Example 5, Example 6, and Example 7). When the mass concentration of the inner layer spinning solution is increased from 0.07 g / mL to 0.27 g / mL, the fluorescence quantum yield of the luminescent material shows a trend of first increasing and then decreasing. When the mass fraction of the inner layer spinning solution is about 0.21 g / mL, the fluorescence quantum yield of the luminescent material reaches a maximum value of 25.6%, achieving high luminescence efficiency in the yellow light band of the lead-free system.
[0139] Fig.13 The fluorescence photographs and fluorescence spectrum change diagram of the luminescent material (Example 1) obtained by using polyvinylidene fluoride as a high molecular polymer placed in water for different days. It can be seen from the figure that the luminescent material prepared by the present invention can be stably maintained in water for more than 30 days, and the fluorescence intensity remains almost unchanged, proving that the CsCu2I3 nanoparticles are protected by the polymer matrix from erosion and decomposition by water molecules, which significantly improves the chemical stability of the luminescent material and lays a foundation for the luminescent material to cope with complex application environments.
[0140] Fig.14 The photo shows a working light-pumped yellow light emitting device that can be directly constructed using luminescent materials and ultraviolet LEDs. The luminescent material prepared in Example 1 is directly covered on the ultraviolet light (wavelength 320 nm) LED lamp bead without any packaging. When the power is turned on, the light-pumped yellow light emitting device emits bright yellow light.
[0141] See also Fig.15 As shown, the fluorescence quantum yields of the luminescent materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested. It can be known that the fluorescence quantum yields of Comparative Example 1 and Comparative Example 2 are significantly lower than that of Example 1 of the present invention, decreased by more than 50%, and even decreased by about 68%. It is analyzed that in Comparative Example 1, cuprous iodide, cesium iodide, etc. are heated and mixed with polyvinylidene fluoride. It should be that heating has a certain negative effect on the formation and yield of CsCu2I3 particles. No hypophosphorous acid is added in Comparative Example 2. It is analyzed that hypophosphorous acid should be beneficial to the formation of CsCu2I3 particles and the increase of yield.
[0142] See also Fig.16 As shown, the stability test of the luminescent material prepared in Comparative Example 3 is carried out. It can be seen from the figure that the fluorescence disappears immediately after it is immersed in water. Fig.16 As shown in Figure b, no yellow light is emitted under ultraviolet light, while the luminescent material prepared in Comparative Example 3 does not have the coating structure of the present invention, which proves that the special structure of the luminescent material of the present invention plays an important role in water stability.
[0143] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0144] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A method for preparing a luminescent material, characterized in that: The preparation method comprises: In the presence of hypophosphorous acid, a copper-based iodide perovskite precursor is dispersed in a first organic solvent, and mixed at 20-30° C. to form a first mixed solution; Mixing the high molecular polymer with a second organic solvent under heating conditions to prepare a second mixed solution; Mixing part of the second mixed solution and the first mixed solution at 20-30° C. to form an inner layer spinning solution, and spinning the remaining second mixed solution as an outer layer spinning solution by coaxial electrospinning to obtain the luminescent material; The mass concentration of the copper-based iodide perovskite precursor in the inner spinning solution is controlled to be 0.15-0.25 g / mL, and the mass ratio of the copper-based iodide perovskite precursor to the high molecular polymer in part of the second mixed solution is 1.1-1.4:
1. The luminescent material is a luminescent fiber or a luminescent aggregate composed of a plurality of the luminescent fibers. The luminescent fiber includes an inner layer and an outer layer coated on the inner layer. The inner layer includes a polymer matrix and CsCu2I3 particles dispersed in the polymer matrix and present in nanometer size. The polymer matrix and the outer layer are each independently formed by a portion of the polymer. The CsCu2I3 particles are formed by converting the copper-based iodide perovskite precursor.
2. The method for preparing a luminescent material according to claim 1, characterized in that: The mass concentration of the copper-based iodide perovskite precursor in the inner layer spinning solution is controlled to be 0.17-0.23 g / mL.
3. The method for preparing the luminescent material according to claim 1 or 2, characterized in that: The ratio of the mass of the high molecular polymer in the inner layer spinning solution to the mass of the high molecular polymer in the outer layer spinning solution is 1:0.9-1.
1.
4. The method for preparing a luminescent material according to claim 1, characterized in that: The copper-based iodide perovskite precursor is composed of CsI and CuI, and the molar ratio of the CsI to the CuI is 1:2.0-2.
05.
5. The method for preparing a luminescent material according to claim 4, characterized in that: Based on 1 mmol of the CsI, the amount of the hypophosphorous acid added is 0.05-0.15 mL, and the hypophosphorous acid is added in the form of a hypophosphorous acid aqueous solution, and the mass fraction of the hypophosphorous acid aqueous solution is 40%-60%.
6. The method for preparing a luminescent material according to claim 1, characterized in that: The mass concentration of the high molecular weight polymer in the second mixed solution is controlled to be 0.1-0.6 g / mL.
7. The method for preparing a luminescent material according to claim 1, characterized in that: The heating condition is controlled at a temperature of 50-80°C.
8. The method for preparing a luminescent material according to claim 1, characterized in that: The process parameters of the coaxial electrospinning method include: a spinning voltage of 15-25 kV, a propulsion speed of 0.1-0.5 mL / h, and a receiving distance of 20-25 cm.
9. The method for preparing a luminescent material according to claim 1, characterized in that: The high molecular polymer is a combination of one or more selected from polyvinylidene fluoride, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol; the first organic solvent and the second organic solvent respectively include N,N-dimethylacetamide and / or N,N-dimethylformamide; and / or the average weight-average relative molecular mass of the high molecular polymer is 100,000-2,000,000.
10. The method for preparing a luminescent material according to claim 1, characterized in that: The photoluminescence quantum yield of the luminescent material is adjusted by the content of the CsCu2I3 particles, and the photoluminescence quantum yield shows a trend of first increasing and then decreasing as the content of the CsCu2I3 particles increases.
11. The method for preparing a luminescent material according to claim 1, characterized in that: A bonding layer is formed between the inner layer and the outer layer, and the bonding layer is formed by the mutual penetration of the high molecular polymers respectively contained in the inner layer and the outer layer; and / or the luminescent aggregate is a film-shaped luminescent film.
12. A luminescent material prepared by the method for preparing a luminescent material according to any one of claims 1 to 11.
13. Use of the luminescent material according to claim 12 in preparing a light-pumped yellow LED device.
14. Use of the luminescent material according to claim 12 in flexible X-ray imaging.
Citation Information
Patent Citations
Photodiode type X-ray detector based on CsCu2I3 wafer as well as preparation method and application of photodiode type X-ray detector
CN115188898A
Preparation method of high-quality large-size Cs3Cu2I5 single crystal scintillator
CN118422338A